Muscles-bearing of sting apparatus in social wasps and their relationship with the autotomy (Hymenoptera: Vespidae: Polistinae) - ManzoliPalma, M. D.; daCunha, M. S.; Gobbi, N. (Assn Advan Zoology, 1997)
The musculature that sustains the stinging organ was studied in three species of social wasps using scanning electron microscopy technique. It were observed some differences among species in which sting autotomy occurs and in which it does not. These differences were related to the diameter,length and position of insertion of these muscles.